The Origin and Distribution of Birds in Coastal Alaska and British Columbia : The Lost Manuscript of Ornithologist Harry S. Swarth - Swarth, Christopher W. (Book collections on Project MUSE., 2022)
"At the time of his death in 1935, Harry S. Swarth, head of the Mammalogy and Ornithology Departments at the California Academy of Sciences in San Francisco, had been preparing a manuscript reflecting on twenty-five years of research in Alaska and British Columbia. "The Distribution and Migrations of Birds in Adjacent Alaska and British Columbia" summarized Swarth's research, ideas, and conjectures on bird life in the region, including theories on when and how birds populated this vast territory after the retreat of glaciers near the end of the Pleistocene. Drawing on his field experiences and the forty scientific papers on the region he published from 1908 on, Swarth's manuscript represented state-of-the-art science for the time. And it holds up; his work is still cited by ornithologists today. In 2019, Christopher Swarth, Harry's grandson and a scientist in his own right, discovered the forgotten manuscript. The edition he proposes here will include the original unpublished manuscript, accompanied by contextual essays from contemporary scientists, including Steven Heinl (Alaska Fish & Wildlife) and Philip Unitt (San Diego Natural History Museum). He has also included excerpts from Harry Swarth's field notes to bring additional color and insight to the project. Appendices include expedition locations, a comprehensive list of Harry Swarth's publications, and a glossary with historic and contemporary bird names"--